1997
DOI: 10.1111/j.1540-4781.1997.tb05497.x
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Instruction of Pragmatic Aspects: Implications of Pragmatic Transfer by American Learners of Japanese

Abstract: This study investigated pragmatic transfer in American learners of Japanese responding to compliments. A closed role play was used to collect interlanguage data from the learners and normative data from Japanese and American native speakers. An Initial Sentence Analysis indicated mat the learners transferred nonuse of avoidance strategies but not of positive strategies. The American normative data suggested a dominant use of positive strategies, whereas a mixture of three strategies was found in the Japanese n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…The counterpart to a compliment is the compliment response, which has been investigated across cultures since the late 1980s (e.g., Chen, 1993;Golato, 2002;Han, 1992;Herbert, 1989;Herbert & Straight, 1989;Lewandowska-Tomaszczyk, 1989;Lorenzo-Dus, 2001;Matsuura, 2002;Nelson, Al-Batal, & Echols, 1996;Saito & Beecken, 1997). Among those studies of cross-cultural comparison, Matsuura (2002) is one of the few studies that illustrates differences between American and Japanese response patterns, and suggests that ostensible acceptance, or light acceptance, of compliments may be characteristic of American English.…”
Section: Previous Studies On Complimentsmentioning
confidence: 99%
“…The counterpart to a compliment is the compliment response, which has been investigated across cultures since the late 1980s (e.g., Chen, 1993;Golato, 2002;Han, 1992;Herbert, 1989;Herbert & Straight, 1989;Lewandowska-Tomaszczyk, 1989;Lorenzo-Dus, 2001;Matsuura, 2002;Nelson, Al-Batal, & Echols, 1996;Saito & Beecken, 1997). Among those studies of cross-cultural comparison, Matsuura (2002) is one of the few studies that illustrates differences between American and Japanese response patterns, and suggests that ostensible acceptance, or light acceptance, of compliments may be characteristic of American English.…”
Section: Previous Studies On Complimentsmentioning
confidence: 99%
“…Research in the area of speech acts has also revealed challenges that learners of Japanese face when performing illocutionary functions (e.g., Furukawa, 2001; Ikoma & Shimura, 1993; Jones, 1998; Kashiwazaki, 1993; Mizuno, 1996; Saito & Beecken, 1997; Sameshima, 1998; Tateyama, 2001). Ikoma and Shimura, for instance, examined the speech act of refusals by native speakers (NSs) of Japanese and American learners of Japanese, revealing several cases of negative transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Compliment upgrading is found but at a low frequency. Thanking, perhaps is not used to signal an agreement with the compliment as often as has been found in previous papers (Holmes, 1988, Nelson, Al-Batal, Echols, 1996Saito & Beecken, 1997;Li & Feng, 2000). On the contrary, the two lowest degrees (level 6 and level 7) were found to outnumber the other levels of accepting Cs (respectively 47.62% and 26.66 %).…”
Section: (She Is Not Obedient She Is Very Naughty)mentioning
confidence: 99%